The Ipswich Touch Test (IpTT) Method for Early Detection of Neuropathy in Patients with Type 2 Diabetes Mellitus at General Practice of Dr. Rewin Dhillon, MBBS, Berastagi - Friska Sembiring; Murni Sari Dewi Simanullang; Larry Gilbert Purba (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease characterized by hyperglycemia resulting from insulin resistance or impaired insulin secretion. One of the most common long-term complications is diabetic neuropathy, which causes peripheral nerve damage and may lead to sensory and motor disturbances, foot ulcers, and amputations. Early detection is essential to prevent disease progression. The Ipswich Touch Test (IpTT) is a simple, non-invasive, and practical screening method suitable for primary care settings. This descriptive study involves 57 patients with T2DM who met the inclusion criteria (aged >20 years, no foot ulcers, and cooperative). Samples are selected using accidental sampling. Neuropathy screening is conducted using the IpTT at six points on both feet with an observation sheet. Data are analyzed univariately and presented as frequencies and percentages. Of the 57 respondents, 50 patients (87.7%) show no signs of neuropathy, while 7 patients (12.3%) are identified as having neuropathy based on IpTT results. Most patients without neuropathy have a duration of diabetes of less than five years (82%), whereas neuropathy was more commonly found in patients with a diabetes duration of five years or more. The prevalence of diabetic neuropathy among patients with T2DM in this practice is relatively low. The duration of diabetes is presumed to be associated with neuropathy due to prolonged exposure to chronic hyperglycemia. Routine use of the IpTT in primary care is recommended for early detection and prevention of diabetic foot complications.